2021
DOI: 10.1111/pim.12834
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive immune responses following PD‐L1 blockade in treating chronic murine alveolar echinococcosis

Abstract: Alveolar echinococcosis (AE) is one of the clinically most severe zoonotic helminthic diseases in humans, caused by the continuous proliferation of the larval stage (metacestode) of Echinococcus multilocularis. Upon ingestion of the E. multilocularis eggs by intermediate hosts such as small rodents and human, echinococcal metacestodes form alveolar structures with multiple vesicles of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Additionally, the present work showed that ABZ treatment ameliorates E. multilocularis infection and almost completely reverses the effects on serum bile acids and gene expression. This further demonstrates the efficacy of ABZ, mainly due to inhibition of parasite proliferation and immune cell infiltration as reported previously [27]. ABZ treatment itself tended to decrease hepatic bile acid concentrations.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Additionally, the present work showed that ABZ treatment ameliorates E. multilocularis infection and almost completely reverses the effects on serum bile acids and gene expression. This further demonstrates the efficacy of ABZ, mainly due to inhibition of parasite proliferation and immune cell infiltration as reported previously [27]. ABZ treatment itself tended to decrease hepatic bile acid concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…In this model, the parasite mostly grows in the peritoneal cavity. A macroscopic and histological assessment in an earlier study [ 27 ] thus did not detect any visible parasitic structures within the livers of any mouse, but inflammatory cell infiltrates with elevated levels of pro-inflammatory cytokines were observed in infected mice. Furthermore, the treatment efficacy of ABZ was demonstrated in the previous study by a significantly reduced parasite weight (isolated from the peritoneal cavity), the histopathology (immune cell infiltration), and reduced liver tissue cytokine levels.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations